PEMANFAATAN TEKNOLOGI INFORMASI PADA PEMBELAJARAN KIMIA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT DI MASA PANDEMI COVID-19 - Victoria Aziz; Abdul Wachid (Chemistry Education Study Program Sriwijaya University, 2022)
Teacher creativity and innovation as facilitators in learning activities are very important. The purpose of this paper is to explain how to study chemistry during a pandemic and to explain how teachers can increase student interest in learning chemistry during a pandemic. The research method used is descriptive qualitative. Learning chemistry during a pandemic can be done by taking advantage of advances in information technology. One of them is by accessing online learning media that has been provided by the Ministry of Education and Culture. Meanwhile, so that students are interested in learning chemistry during a pandemic, it can be done by providing worksheets that can make students work on assignments creatively. As well as making use of tools and materials in the surrounding environment.